Socialization of Product Packaging Efforts to Increase Competitiveness for MSMEs in Tambak Bulak Sidoarjo - Virginia Mandasari; Mentari Clara Dewanti; Fauzatul Laily Nisa; Anisa Fitria Utami (Nusantara Science and Technology Proceedings, 2023)
Food is a basic human need that comes from natural resources and most of it is also produced by home industries which have been processed into various types of food. The high demand for food has become a very important concern for the government to ensure that food is safe for consumption by all consumers. One form of guarantee issued by the government is a PIRT (home industrial food) permit. PIRT is a food production permit produced by home industry scale businesses. This permit is an official letter issued by BPOM (Food and Drug Monitoring Agency). The problem experienced by the "Ramajaya" Sweet Sticky Tape Producer is that he does not yet have a PIRT permit for the business he is running so he is still having difficulty marketing his products to various mini markets and supermarkets in Sidorjo Regency because he does not yet have production guarantees in the form of PIRT and the packaging used as well. still simple and not by government standards. This community service aims to help the business of the "Ramajaya" Sweet Glutinous Tape Producer to obtain a legal permit for products suitable for distribution in the form of a PIRT permit from the government through assistance in obtaining a PIRT permit at the Sidoarjo Regency Health Service office and also providing outreach regarding the importance of PIRT and providing options for change the packaging used.